Death of the Lethargic: Effects of Expansion into New Technical Subfields on Performance in a Firm's Base Business - Mitchell, Will; Singh, Kulwant (Organization Science, 1993)
This paper finds that industry incumbents that do not expand into new technical subfields tend to fare poorly in their established businesses, even if the market for the established products continues to exist. Firms that expand from their established businesses survive longer and achieve greater subsequent market share than competitors that do not expand. By some measures, however, a failed attempt to expand into a new subfield may be even more harmful to a base business than nonexpansion. The study employs conventional and accelerated event-time regression models to analyze market share and survival. The sample, which includes 371 incumbents in four base subfields of the medical diagnostic imaging industry between 1953 and 1989, examines performance following the emergence of five new technical subfields of the industry.